Social inequity in maternal health - Javier Eslava-Schmalbach (Federación Colombiana de Obstetricia y Ginecología, 2010)
Reflecting on an umbrella term for social inequities in health leads to two all-embracing principles being assumed; the first is that not all forms of inequality found in health are included in its definition but only those being labelled inequity as they arise from inequality which is avoidable, unnecessary and unjust.1 The second is related to that known as social inequality which describes inequity as being a consequence or product of situations which society can avoid.2,3 The panorama for analysis thus ranges from what is very general, which would be health inequality, to something more specific such as social inequity in health in which society, the decisionmaker, and health care in the social security system must bear high levels of responsibility.